Teaching and learning adaptive hydrometallurgy-nanohydrometallurgy - Pešić B. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The weakness of the U.S. mining industry has caused a significant decline in academic programs in mining and metallurgical engineering in the U.S. The author’s view on the reasons for such weaknesses is presented in a historical prospective covering some key events within the last 30 years. Arguably, the decline of U.S. mining industry is due to many reasons, the most important being the lack of modernization, the difficulty to comply with stringent environmental laws, and global market forces, are the most important. The importance of emerging nanotechnologies is viewed as an opportunity for the evolution of one component of metallurgical engineering - hydrometallurgy - into nanohydrometallurgy, thus extending its viability.